THE THREE-YEAR SURVIVAL RATE OF CERVICAL CANCER PATIENTS AT REFERRAL HOSPITAL IN SOUTHERN SUMATRA, INDONESIA - Zubaidah Zubaidah; Rico Januar Sitorus; Rostika Flora; Kraichat Tantrakarnapa (Jurnal Berkala Epidemiologi, 2022)
Background: Cervical cancer is the second most common cancer and the third leading cause of death in Indonesia. Purpose: This study aims to identify the 3-year survival rate of cervical cancer patients and its prognostic factors in a referral hospital in Southern Sumatra, Indonesia. Methods: Cohort retrospective study using secondary data from medical records of cervical cancer patients from January 2014 until December 2016. Data of each patient was evaluated for 36 months since the patients were firstly diagnosed with cervical cancer. Kaplan Meier curve was used to determine the survival rate and identify the proportional hazard assumption. The Cox regression model was utilized to determine the survival rate and Hazard Ratio (HR). Results: There were 274 of 799 cervical cancer patients who met the inclusion criteria. The 3-year survival rate for cervical cancer patients at survival rate was around 65%, and prognostic factors related to the survival of cervical cancer patients with p-value <0.05, i.e. age (HR=0.51; 95%CI=0.29-0.90), metastasis (HR=2.43; 95%CI=1.28-4.61), and completeness of therapy (HR=7.23; 95%CI=3.82-13.71. The complication was a confounding factor with metastasis and survival rate. Conclusion: The 3-year survival rate for cervical cancer patients at Mohammad Hoesin Hospital Palembang (RSMH) was 65%. The prognostic factors for the survival rate were age, metastasis, and completeness therapy. It was essential for cervical cancer patients to adhere to the therapy program recommended by doctors to increase the survival rate.